Opposite effects of acute and chronic IGF1 on rat dorsal root ganglion neuron excitability - Pastor, Jennyfer; Attali, Bernard (Frontiers in Cellular Neuroscience, 2024)
Insulin-like growth factor-1 (IGF-1) is a polypeptide hormone with a ubiquitous distribution in numerous tissues and with various functions in both neuronal and non-neuronal cells. IGF-1 provides trophic support for many neurons of both the central and peripheral nervous systems. In the central nervous system (CNS), IGF-1R signaling regulates brain development, increases neuronal firing and modulates synaptic transmission. IGF-1 and IGF-IR are not only expressed in CNS neurons but also in sensory dorsal root ganglion (DRG) nociceptive neurons that convey pain signals. DRG nociceptive neurons express a variety of receptors and ion channels that are essential players of neuronal excitability, notably the ligand-gated cation channel TRPV1 and the voltage-gated M-type K + channel, which respectively triggers and dampens sensory neuron excitability. Although many lines of evidence suggest that IGF-IR signaling contributes to pain sensitivity, its possible modulation of TRPV1 and M-type K + channel remains largely unexplored. In this study, we examined the impact of IGF-1R signaling on DRG neuron excitability and its modulation of TRPV1 and M-type K + channel activities in cultured rat DRG neurons. Acute application of IGF-1 to DRG neurons triggered hyper-excitability by inducing spontaneous firing or by increasing the frequency of spikes evoked by depolarizing current injection. These effects were prevented by the IGF-1R antagonist NVP-AEW541 and by the PI3Kinase blocker wortmannin. Surprisingly, acute exposure to IGF-1 profoundly inhibited both the TRPV1 current and the spike burst evoked by capsaicin. The Src kinase inhibitor PP2 potently depressed the capsaicin-evoked spike burst but did not alter the IGF-1 inhibition of the hyperexcitability triggered by capsaicin. Chronic IGF-1 treatment (24 h) reduced the spike firing evoked by depolarizing current injection and upregulated the M-current density. In contrast, chronic IGF-1 markedly increased the spike burst evoked by capsaicin. In all, our data suggest that IGF-1 exerts complex effects on DRG neuron excitability as revealed by its dual and opposite actions upon acute and chronic exposures.